What Qualities Are Most Important to Making a Point of Care Test Desirable for Clinicians and Others Offering Sexually Transmitted Infection Testing? - Hsieh, Yu-Hsiang (Public Library of Science, 2011)
BACKGROUND: To investigate the possible effects of different levels of attributes of a point-of-care test (POCT) on sexually transmitted infection (STI) professionals' decisions regarding an ideal POCT for STI(s). METHODS: An online survey was designed based on a large-scale in-depth focus discussion study among STI experts and professionals. The last section of the survey “build your own POCT” was designed by employing the discrete choice experiment approach. Practicing clinicians from two venues, STI-related international conference attendees and U.S. STD clinic clinicians were invited to participate in the survey. Conditional logistical regression modeling was used for data analysis. RESULTS: Overall, 256 subjects took the online survey with 218 (85%) completing it. Most of the participants were STD clinic clinicians who already used some POCTs in their practice. “The time frame required” was identified as a major barrier that currently made it difficult to use STI POCTs. Chlamydia trachomatis was the organism chosen as the top priority for a new POCT, followed by a test that would diagnose early seroconversion for HIV, and a syphilis POCT. Without regard to organism type selected, sensitivity of 90–99% was always the most important attribute to be considered, followed by a cost of $20. However, when the test platform was prioritized for early HIV seroconversion or syphilis, sensitivity was still ranked as most important, but specificity was rated second most important. CONCLUSIONS: STI professionals preferred C. trachomatis as the top priority for a new POCT with sensitivity over 90%, low cost, and a very short completion time.